Incidence of common nerve injuries in patients with oral and maxillofacial trauma present at tertiary care hospital - Ali, Sarfraz; Jehan Alam; Shah, Ruqayah; Sohail, Ahmad (Medical Journal of South Punjab, 2024)
Objective: To determine the frequency of common nerve injuries among patients presented with maxillofacial trauma.Methodology: The study was designed as a cross-sectional study and conductedin the Department of Oral and Maxillofacial Surgery at Jinnah Postgraduate Medical Centre, Karachi, from November 2023 to May 2024. A detailed history was obtained from each patient, followed by a clinical examination to identify any nerve involvement due to maxillofacial trauma. Radiological evaluation in the form of Orthopantomogram (OPG) and Paranasal Sinus (PNS) views was carried out to assess the presence of fractures and any associated nerve injuries. The type of nerve injury was confirmed through a comprehensive clinical assessment and history to detect involvement of the olfactory, infraorbital, inferior alveolar, and facial nerves.Results: Mean age was 32.4 ± 11.7 years. The majority of patients were male (70.0%), with females comprising 30.0% of the study population. In terms of type of nerve injury, the inferior dental nerve (IDN) was most commonly affected (44.6%), followed by the infraorbital nerve (ION) (28.5%), the facial nerve (18.5%), and the olfactory nerve (8.5%).Conclusion: This study's findings align with global trends in oral and maxillofacial nerve injuries, showing male predominance and high RTA-related trauma incidence, though assaults are more common in developed nations, reinforcing known trauma-nerve injury associations.